Trade-off Improvements by Combining EGR and Supercharging Ignited by Next Generation Bio-alcohol Blended FAME Fuels in Diesel Dual Fuel Operation Using Natural Gas - Yoshimoto, Yasufumi; Kinoshita, Eiji; Otaka, Takeshi (Frontiers in Mechanical Engineering, 2020)
Studies in diesel dual fuel (DDF) operation which introduce compressed natural gas (CNG) from the intake pipe and ignite it by a diesel fuel injection in the combustion chamber have been conducted using conventional diesel engines. The present study investigated the effects of trade-off improvements between NOx and smoke emissions with next generation bio-alcohol blended FAME fuels ignition in DDF operation with a combination of EGR and supercharging. The CNG supply rates were set at 0% (ordinary diesel operation) and at 41-44% (DDF operation) on a heat energy basis, the boost pressures were set to two conditions with supercharger operation: 100 kPa (naturally aspirated operation, N/A) or 120 kPa (supercharged operation, S/C), and the EGR rates were varied from 0 to 25%. Blended fuels with a base fuel vs. alcohol ratio of 7: 3 were prepared using what in the following is termed PLME containing equal proportions of methyl palmitate (PME) and methyl laurate (LME) as the base fuel. The next-generation bio-alcohols used here were iso-pentanol (C5) and iso-butanol (C4), and the engine performance, combustion characteristics, and exhaust emissions were investigated with iso-pentanol blended PLME (termed PLiP30), iso-butanol blended PLME (PLiB30), and neat PLME, as the ignition fuel. The results showed that regardless of ignition fuel, the DDF operation combining cooled EGR and supercharging improved the trade-off relation between NOx and smoke emissions significantly while maintaining relatively high brake thermal efficiencies.